1977
DOI: 10.1088/0031-9155/22/6/006
|View full text |Cite
|
Sign up to set email alerts
|

Lyoluminescence dosimetry in photon and fast neutron beams

Abstract: The lyoluminescence (LL) technique using mannose, a monosaccharide, is described. Dose-response curves for 60Co-gamma-rays (5 rad to 120 krad), fission neutrons, 5.3 MeV and 15 MeV neutrons (100 rad to 20 krad) have been measured. The close tissue-equivalence of mannose makes this material well suited for dosimetric use in low energy X-ray fields for radiotherapy and radiobiology. It also provides a cheap, simple and reproducible dosemeter in industrial applications of radiation (sprouting inhibition of onions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1981
1981
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Detection limit estimated around 0.5 Gy did not allow estimating dose in the steady state experiment. Mannose results are consistent with the literature; for instance, with lyoluminescence techniques; Puite et al (16) and Ettinger et al found respectively a response relatively to 60 Co gamma rays of 0.34 for ®ssion neutrons and 0.2 for 1 MeV neutrons. As for commercial sugar, mannose showed a time dependence shape line spectrum modi®cation, which was already observed by Bartlett et al (28) .…”
Section: Mannosesupporting
confidence: 90%
See 1 more Smart Citation
“…Detection limit estimated around 0.5 Gy did not allow estimating dose in the steady state experiment. Mannose results are consistent with the literature; for instance, with lyoluminescence techniques; Puite et al (16) and Ettinger et al found respectively a response relatively to 60 Co gamma rays of 0.34 for ®ssion neutrons and 0.2 for 1 MeV neutrons. As for commercial sugar, mannose showed a time dependence shape line spectrum modi®cation, which was already observed by Bartlett et al (28) .…”
Section: Mannosesupporting
confidence: 90%
“…Mannose, whose neutron response was already studied by lyoluminescence (16,17) , was also investigated as an EPR material for criticality dosimetry.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the lower limit of detection of radiation dose was improved down to 10 mGy (1 rad) using a special sample of trehalose dihydrate. For most saccharides, the lyoluminescence dependence on radiation dose is fairly linear up to l kGy (100 krad) with a variation in linearity ranging between 10-20% (Atari 1973 Investigation of the lyoluminescence response of saccharides to radiations of different linear energy transfer (LET) including protons, a-particles, 3He2+ and neutrons have indicated a dependence on the radiation quality (Puite and Crebolder 1977, Ettinger et a1 1980, Bartlett and Edwards 1980. Some of these studies used mannose and glucose.H20 irradiated by negative pions produced at the Rutherford Laboratory, UK (Bartlett et a1 1981).…”
Section: Introductionmentioning
confidence: 99%
“…For most saccharides, the lyoluminescence dependence on radiation dose is fairly linear up to l kGy (100 krad) with a variation in linearity ranging between 10-20% (Atari 1973). 0031-9155/83/050493 + 10$02.00 @ 1983 The Institute of Physics Investigation of the lyoluminescence response of saccharides to radiations of different linear energy transfer (LET) including protons, a-particles, 3He2+ and neutrons have indicated a dependence on the radiation quality (Puite and Crebolder 1977, Ettinger et a1 1980, Bartlett and Edwards 1980. Some of these studies used mannose and glucose.H20 irradiated by negative pions produced at the Rutherford Laboratory, UK (Bartlett et a1 1981).…”
Section: Introductionmentioning
confidence: 99%